Social Media Use and Cardiovascular Health Among US High School Students - Ryan Saelee; Izraelle I. McKinnon; Sandra J. Kiplagat; Jelonia T. Rumph; Caitlin L. Merlo; Kelly Cornett; Sandra Leonard; Ahlia Sekkarie; Kathleen H. Krause; Jonetta Mpofu (Public Health Reports®, 2026)
Objectives: Cardiovascular health during adolescence can shape cardiovascular disease risk later in life. We examined the association between frequent social media use and cardiovascular health among US high school students. Methods: We used data from the 2023 national Youth Risk Behavior Survey to create cardiovascular health metrics based on the American Heart Association’s Life’s Essential 8 construct (range, 0-100), with a higher score representing better cardiovascular health. Metrics included diet, physical activity, nicotine exposure, sleep health, body mass index, and an overall cardiovascular health score. We dichotomized social media use as frequent social media use versus infrequent social media use/nonuse. Linear regression estimated the association between social media use and cardiovascular health metrics by sex, adjusting for grade and race and ethnicity. Results: Frequent social media use was associated with significantly lower mean scores for overall cardiovascular health (female: β = −5.3; 95% CI, −7.5 to −3.1; male: β = −3.6; 95% CI, −5.3 to −1.9), diet (female: β = −9.3; 95% CI, −12.1 to −6.5; male: β = −6.4; 95% CI, −9.2 to −3.5), and nicotine exposure (female: β = −11.9; 95% CI, −17.1 to −6.8; male: β = −10.7; 95% CI, −14.8 to −6.6) compared with infrequent/nonuse. Among male students only, frequent social media use was associated with a significantly higher mean physical activity score (β = 4.4; 95% CI, 0.6 to 8.2) but a lower mean sleep health score (β = −4.8; 95% CI, −8.3 to −1.3). Conclusions: Future studies could examine the mechanisms linking frequent social media use with cardiovascular health among adolescents to better inform prevention strategies.